Visualization of cristae and mtDNA interactions via STED nanoscopy using a low saturation power probe - Ren, Wei; Ge, Xichuan; Li, Meiqi; Sun, Jing; Li, Shiyi; Gao, Shu; Shan, Chunyan; Gao, Baoxiang; Xi, Peng (Light, science & applications, 2024)
Mitochondria are crucial organelles closely associated with cellular metabolism and function. Mitochondrial DNA (mtDNA) encodes a variety of transcripts and proteins essential for cellular function. However, the interaction between the inner membrane (IM) and mtDNA remains elusive due to the limitations in spatiotemporal resolution offered by conventional microscopy and the absence of suitable in vivo probes specifically targeting the IM. Here, we have developed a novel fluorescence probe called HBmito Crimson, characterized by exceptional photostability, fluorogenicity within lipid membranes, and low saturation power. We successfully achieved over 500 frames of low-power stimulated emission depletion microscopy (STED) imaging to visualize the IM dynamics, with a spatial resolution of 40 nm. By utilizing dual-color imaging of the IM and mtDNA, it has been uncovered that mtDNA tends to habitat at mitochondrial tips or branch points, exhibiting an overall spatially uniform distribution. Notably, the dynamics of mitochondria are intricately associated with the positioning of mtDNA, and fusion consistently occurs in close proximity to mtDNA to minimize pressure during cristae remodeling. In healthy cells, >66% of the mitochondria are Class III (i.e., mitochondria >5 μm or with >12 cristae), while it dropped to <18% in ferroptosis. Mitochondrial dynamics, orchestrated by cristae remodeling, foster the even distribution of mtDNA. Conversely, in conditions of apoptosis and ferroptosis where the cristae structure is compromised, mtDNA distribution becomes irregular. These findings, achieved with unprecedented spatiotemporal resolution, reveal the intricate interplay between cristae and mtDNA and provide insights into the driving forces behind mtDNA distribution. HBmito Crimson has the ability to localize specifically on the inner mitochondrial membrane and emit light, while its superior photostability enables STED imaging.